Electronic transport driven by collective light-matter coupled states in a quantum device - Pisani, Francesco; Gacemi, Djamal; Vasanelli, Angela; Li, Lianhe; Davies, Alexander Giles; Linfield, Edmund; Sirtori, Carlo; Todorov, Yanko (Nature communications, 2023)
In the majority of optoelectronic devices, emission and absorption of light are considered as perturbative phenomena. Recently, a regime of highly non-perturbative interaction, ultra-strong light-matter coupling, has attracted considerable attention, as it has led to changes in the fundamental properties of materials such as electrical conductivity, rate of chemical reactions, topological order, and non-linear susceptibility. Here, we explore a quantum infrared detector operating in the ultra-strong light-matter coupling regime driven by collective electronic excitations, where the renormalized polariton states are strongly detuned from the bare electronic transitions. Our experiments are corroborated by microscopic quantum theory that solves the problem of calculating the fermionic transport in the presence of strong collective electronic effects. These findings open a new way of conceiving optoelectronic devices based on the coherent interaction between electrons and photons allowing, for example, the optimization of quantum cascade detectors operating in the regime of strongly non-perturbative coupling with light. Here the authors investigate the electronic transport in microcavity-coupled quantum detector with strong collective electronic resonances. Their findings present a way to optimize photodetectors operating in the ultra-strong light-matter coupling regime.